REMUNESASI, PENGAWASAN, KONDISI KERJA, FASILITAS KERJA DAN KEPUASAN KERJA (Pegawai Kecamatan Muara Jawa) - Elfreda Aplonia Lau, Ica Ida Wati, Robin Jhonatan, (EKONOMIA, 2015)
The purpose of this study was to determine the Influence of remuneration, supervision, working conditions, working facilities, job satisfaction and effectiveness To determine the extent of the influence of remuneration, supervision, working conditions, working facilities on job satisfaction.Formulation of the problem is the Are Remuneration significant effect on job satisfaction, Is Monitoring significant effect on job satisfaction, Is Working Conditions have a significant effect on job satisfaction, Is Work Facilities significant effect on job satisfaction, What Remuneration, Supervision, Working Conditions and Working Facilities influence on satisfaction of employees working in the office Muara Jawa.Basic theory used is the human resources or manpower abbreviated SDM is that every human being. SDM consists of physical power and think every human being. Strictly speaking every human ability is determined by fikir power and physical power. Human or human resources becomes a key element in any activities conducted. Reliable equipment and advanced without the active role of HR does not mean anything.In this study, the hypothesis can be stated as follows:H 1. Remuneration significant effect on job satisfaction,H 2. Supervision significant effect on job satisfaction,H 3. Working conditions have a significant effect on job satisfaction,H 4. Facility significant effect on job satisfaction,H5. Remuneration, Supervision, Working Conditions, Job Facility jointly significant effect on job satisfaction.The sampling technique used in this research is purposive sampling. The research instrument in this study using the Continuous scale Rating Scale. As for the data collection technique using a questionnaire.Results of this study to obtain the effect of four jointly basically classified as large or very strong, and based on Fisher test (Test-F) to prove that the effect is significant, because the F counted much larger than F table